Pengaruh Marketing Mix 5Cs Terhadap Loyalitas Nasabah Melalui Kepuasan Nasabah Bank Syariah Indonesia Tangerang Selatan - Riski Eka Lestari; Endah Meiria; Desmadi Saharuddin (ITB AAS INDONESIA Surakarta, 2023)
This study aims to analyze the Effect of Marketing Mix 5Cs (Conformity, Character, Commitment, Conscience and Customer Centrism) on Customer Loyalty through Customer Satisfaction of BSI South Tangerang. This research is a quantitative study using Multiple Linear Regression and Sobel Test through Microsoft Excel 2010 and SPSS version 26. The population of this research is BSI South Tangerang customers, 100 respondents were taken as a sample using purposive sampling technique. The results showed that the 5Cs Marketing Mix simultaneously had a significant effect on customer satisfaction and there was a significant effect on customer loyalty. Partially, Conformity has a positive and significant effect on Customer Satisfaction, while Character, Commitment, Conscience and Customer Centrism have no significant effect. Likewise Commitment and Customer Satisfaction have a positive and significant effect on Customer Loyalty, while Conformity, Character, Conscience and Customer Centrism have no significant effect. The results of the Sobel test show that Customer Satisfaction as an intervening variable is able to mediate Conformity to Customer Loyalty, while Character, Commitment, Conscience and Customer Centrism to Customer Loyalty are unable to be mediated by Customer Satisfaction. So this shows that the 5Cs Marketing Mix of Bank Syariah Indonesia (BSI) South Tangerang is quite satisfying but has not been able to increase customer loyalty. Therefore BSI must improve the quality of service to customer needs.